Are There Positive Words in Marketing? A Study on the Vibrational Frequency of Marketing Words - Adriana Manolică; Antoneta Ciobăniță; Raluca-Alexandra Jelea (Ovidius University Annals: Economic Sciences Series, 2020)
The words we use are our true mirrors. What we write, think and talk show our true personality and these words are energy, measured by vibration and frequency. If this is so, that means also that marketing words have their own energy, measured by vibration and frequency and maybe that is the reason we consider them as being positive or negative, from the perspective of the sender or the receiver. This paper presents an experiment conducted on students from Romania and USA, in which we measure the vibration of English spoken words used in Marketing. The aim is to see if we can speak about positive words and if these words actually sell. We want to compare the results between two groups, both fluent in English, but some of them being natives and the others not.